Levi Woodbury family papers - Woodbury, Levi, 1789-1851.; Cahoone, John.; Fox, Gustavus Vasa, 1821-1883.; Fox, Virginia L. Woodbury; Woodbury, Charles Levi, 1820-1898.; Woodbury, Levi, active 1780-1781.
Correspondence, diaries, speeches and writings, financial and legal papers, genealogical notes, autograph collections, scrapbooks, clippings, and other papers chiefly of Levi Woodbury and also of his son, Charles Levi Woodbury, and other family members.
Papers of Levi Woodbury document his service as U.S. secretary of the navy in Andrew Jackson's cabinet, U.S. secretary of the treasury in the Jackson and Martin Van Buren administrations, U.S. senator from New Hampshire, governor of New Hampshire, lawyer, and judge. Subjects include the second Bank of the United States, removal of deposits, the specie circular, panic of 1837, operation of customs houses and land offices, and local and presidential elections of 1824, 1828, 1836, 1840, and 1844. Correspondents include George Bancroft, Thomas Hart Benton, John Helferstein, Isaac Hill, Jesse Hoyt, Henry Hubbard, Andrew Jackson, Dutee Jerauld Pearce, Robert Rantoul, William C. Rives, Richard Rush, Martin Van Buren, Nathaniel West, Campbell Patrick White, and Silas Wright.
Papers of Charles Levi Woodbury (1820-1898), state legislator and U.S. district attorney, of Boston, Mass., include material relating to the U.S.-Canadian fisheries dispute in the 1880s, the seizure of U.S. vessels, and Woodbury's work toward modification of the Washington Treaty of 1871; the Morse telegraph patent; and the estate of Mary A. Taylor. Correspondents include William L. Putnam, George Washington Steele, Charles H. Woodbury, and Gordon Woodbury.
Also includes correspondence between Levi Woodbury and his wife, Elizabeth Williams Clapp Woodbury; journal (1829) kept by Capt. John Cahoone aboard the Vigilant; ships's logs (1780-1781) kept by Capt. Levi Woodbury; correspondence (1861-1865) and naval documents of Gustavus Vasa Fox; diary (1860-1878) and correspondence of Virginia L. Woodbury Fox; two Indian treaties (1713, 1717); contemporary copies of letters from King Charles II and Queen Anne of Great Britain; and letter (1777) from John Hancock to his wife. Other persons represented include Isaac O. Barnes, Montgomery Blair, Asa Clapp, Asa W.H. Clapp, Nehemiah Eastman, and Ellen C.D.Q. Woodbury.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
U.S. senator from and governor of New Hampshire, U.S. secretary of the navy, U.S. secretary of the treasury, and Supreme Court justice, and lawyer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anne, -- Queen of Great Britain, -- 1665-1714 -- Correspondence; Bancroft, George, -- 1800-1891 -- Correspondence; Barnes, Isaac O; Benton, Thomas Hart, -- 1782-1858 -- Correspondence; Blair, Montgomery, -- 1813-1883.; Charles -- II, -- King of England, -- 1630-1685 -- Correspondence; Clapp, Asa, -- 1762-1848.; Clapp, Asa W. H. -- 1805-1891.; Eastman, Nehemiah, -- 1782-1856.; Hancock, John, -- 1737-1793 -- Correspondence; Helferstein, John -- Correspondence; Hill, Isaac, -- 1789-1851 -- Correspondence; Hoyt, Jesse -- Correspondence; Hubbard, Henry, -- 1784-1857 -- Correspondence; Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845 -- Correspondence; Morse, Samuel Finley Breese, -- 1791-1872.; Pearce, Dutee Jerauld, -- 1789-1849 -- Correspondence; Putnam, William L. -- 1835-1918 -- Correspondence; Rantoul, Robert, -- 1805-1852 -- Correspondence; Rives, William C. -- 1793-1868 -- Correspondence; Rush, Richard, -- 1780-1859 -- Correspondence; Steele, George Washington, -- 1839-1922 -- Correspondence; Taylor, Mary A; Van Buren, Martin, -- 1782-1862.; Van Buren, Martin, -- 1782-1862 -- Correspondence; West, Nathaniel, -- 1794-1864 -- Correspondence; White, Campbell Patrick, -- 1787-1859 -- Correspondence; Woodbury, Charles H. -- Correspondence; Woodbury, Ellen C. D. Q. -- -1909.; Woodbury, Gordon, -- 1863- -- Correspondence; Wright, Silas, -- 1795-1847 -- Correspondence; Woodbury family; United States. -- Congress. -- Senate; United States. -- Department of the Treasury; United States. -- Navy -- History; United States. -- Navy Department; Bank of the United States (1816-1836); Vigilant (Ship); Bank deposits; Currency question -- United States; Customs administration -- United States; Elections -- United States -- 19th century; Finance, Public -- United States; Financial crises -- United States -- 19th century; Fisheries -- Canada; Fisheries -- United States; Indians of North America -- Treaties; Presidents -- United States -- Election; Public lands -- United States -- 19th century; Public prosecutors -- Massachusetts -- Boston; Seizure of vessels and cargoes; Telegraph -- Patents; Great Britain. -- 1871 May 8.; New Hampshire -- Politics and government -- 1775-1865.; United States -- Politics and government -- 19th century; Cabinet officers; Governors -- New Hampshire; Jurists; Lawyers